Eksistensi Lembaga Pemberdayaan Masyarakat (LPM) dalam Mewujudkan Pembangunan Desa di Desa Datah, Kecamatan Abang, Kabupaten Karangasem - I Gede Andik Surya Dana; Ida Ayu Putu Widiati; I wayan arthanaya (Warmadewa Press, 2022)
Community empowerment institutions are one form of village institutions in realizing community welfare. The welfare of people's lives must be realized by creating an equal distribution of rights and obligations of the surrounding community. The government in its efforts to realize it is ready with various program arrangements to support this. This research is focused on knowing the existence of Community Empowerment Institutions (LPM), as well as obstacles and efforts in realizing village development carried out by Community Empowerment Institutions (LPM) in Datah Village, Abang District, Karangasem Regency. The method used is an empirical legal approach by seeking information and data directly in the field. Research findings reveal that the existence of LPM in Datah village in village development still needs to be improved. The village government must try to find the obstacles or inhibiting factors that occur, as well as the efforts made so that the LPM program can be said to be effective in the context of village development that aims to prosper the community. Based on the results of the study, it can be concluded that the existence of LPM in Datah village has not had a significant impact and is fully felt by the community. The government needs to increase the empowerment of this institution so that it has a good influence on the progress of the local community.